Osoba w spektrum autyzmu jako pokrzywdzony w polskim procesie karnym. Czy jest to proces równych szans w aspekcie standardów strasburskich? - Sowała, Marcin (PRAWO i WIĘŹ, 2025)
The aim of the paper is to analyse the extent to which the rules of criminal procedure allow for equal opportunities for victims of autism spectrum disorder in the course of Polish criminal proceedings, in order to implement the Strasbourg standards. In his publication, the author presents the special needs of people on the autism spectrum. Due to their disability, these people can exercise their right to go to court, provided that they are provided with appropriate procedural solutions. The author then outlined the Strasbourg standards defined by the European Court of Human Rights in its judgments on the right to a court. The analysis shows that the Court recommends the introduction of specific mechanisms to enable each person to actually benefit from the criminal justice system. A detailed analysis was then carried out of the Polish criminal procedure rules, which can equalise opportunities for victims on the autism spectrum to access criminal proceedings. The analysis was based mainly on the new provision, Article 185e of the Code of Criminal Procedure. The author drew specific scientific conclusions from the analysis. First of all, it was noted that certain mechanisms have recently been introduced, thanks to which an autistic person, as an aggrieved party, has a greater influence on the course of his or her case. However, there are still some shortcomings that need to be addressed. The author has therefore formulated some de lege ferenda postulates.